Statistical Literacy Analysis Viewed from Curiosity in PBL Assisted by the Sway Application - Setiani, Nurokhmi Wahyu; Waluya, Budi; Dewi, Nuriana Rachmani; Herdian, Herdian (AlphaMath : Journal of Mathematics Education, 2024)
This research aims to: (1) analyze the effectiveness of PBL assisted by the Sway application on students' curiosity and statistical literacy; (2) describe students' statistical literacy in PBL learning assisted by the Sway application in terms of curiosity. The research uses mixed methods. The research subjects were students of XII TKJ, SMK Komputama Jeruklegi. The research results obtained: (1) PBL learning assisted by the Sway application is effective for students' statistical literacy; (2) statistical literacy patterns were found for each curiosity category, such as: (a)students with very high curiosity, very able to fulfill indicators of understanding data and drawing conclusions, able to calculate, present and interpret data; (b)students with high curiosity, very capable of meeting the indicators of understanding data and drawing conclusions, able to calculate, present and interpret data with few errors; (c)students with moderate curiosity, able to fulfill the indicators of understanding, calculating, presenting data and drawing conclusions, quite capable of interpreting data; (d)low curiosity students, able to fulfill the indicators of understanding, calculating and presenting data, quite capable of interpreting data and drawing conclusions; (e)students' curiosity is very low, they are quite able to fulfill the indicators of understanding data and are not yet able to calculate, present, draw conclusions and interpret data. Based on research, it is known that there is an influence of curiosity after learning the PBL model assisted by the Sway application of 51.9%. Teachers are advised to use PBL assisted by the Sway application to increase students' statistical literacy